Macroeconomic Policy Rules in Theory and in Practice - Christopher Allsopp (Bank of England, External Monetary Policy Committee Unit, 2002)
This paper discusses the two-way interaction between policy and academic enquiry regarding rules for monetary policy. The emerging consensus on monetary policy is described; in that context, some of the features of the current UK system are outlined which seem particularly important. From a political-economy point of view, what really matters is that an appropriate policy framework should be instituted with the right general properties; a second set of questions, about improving or even optimising performance, can then be considered. Early worries that publicly-expressed disagreements, and public knowledge of closely-split votes, would work against the credibility of the UK system, now appear unfounded. The relevant meaning of 'credibility' of policy is a reputation for competence and trust in the system, and it is argued that the UK system has achieved this reputation. In addition, the monetary policy system in the UK is as transparent and accountable as any in the world. It is argued that the potential costs to credibility and transparency weigh heavily against giving the interest rate another role (e.g. responding to asset-price bubbles) beside pursuit of the inflation target. The paper concludes with some remarks on forecasting procedures in the face of structural change, and on the appropriate combination of monetary and fiscal policy.
Keywords: 330